PERANCANGAN DAN OPTIMALISASI KINERJA JARINGAN HOTSPOT SERVER BERBASIS MIKROTIK PADA SMK NEGERI 2 DOMPU - Joko Triyono; Rahmad Ramadhan; Prita Haryani (Jurnal Informatika Komputer, Bisnis dan Manajemen, 2021)
SMK Negeri 2 Dompu is one of the vocational high schools located in Dompu Regency, the school already has a wireless network, but the large number of uses in one access point device results in an unstable internet network or the network being slow because it has not used an optimal configuration. The proxy-based Hotspot Server network uses the Mikrotik Simple Queue feature at schools to centrally manage hotspot networks and can manage bandwidth evenly. The method used in this research is the data collection method, namely the method of observation and literature study methods, the method of quantitative data analysis using network performance parameters namely delay, throughtput, packet loss and the Wireshark application. The results of designing and optimizing the performance of the Mikrotik-based Hotspot Server network at schools can run well and Bandwidth management has been successfully managed by Simple Queue. In the throughput test, the average result is 46.9% KB. The average packet loss results are 0%, because after analyzing all packets there are no missing packets or in other words all packets have been sent to the destination. While Delay get an average result of 39 ms